Photochromic hybrid sol-gel films containning naphtopyrans - Coelho, Paulo J. (2010)
Several photochromic benzo- and naphthopyrans were embedded in hybrid organic-inorganic ureasilicate based films obtained by a sol-gel process. The resulting films, containing 0,1 % (w/w) of the photochromic compound, were transparent and flexible and for naphthopyrans they were colourless or presented just a slight colouration. Under UV continuous irradiation the films developed a significant absorption in the visible region that fades in the dark with variable kinetics depending on the naphthopyran structure. 2,2-Diphenyl-3H-naphtho[2,1-b]pyran films showed a very fast colouration under UV light giving rise to coloured open forms, containing mainly the TC isomer (98%) along with a very small amount of the more stable TT isomer (2%), that practically returned to the initial absorbance in one minute.